From Sitting in a Gallery to Sitting at a Table. School Furniture in Early Childhood Education in the 19th Century - Sanchidrián-Blanco, María del Carmen; Molina Poveda, María Dolores (My University, 2022)
The main change that ever happened in early childhood education was the introduction of a table where children could do things (draw, or manipulate, for example). The first infant schools were created in Spain in 1838 to collect and educate children aged two to six years old whose mothers could not look after them because they were working. Children sat in a gallery where they could just listen and repeat what was said. In the late 19th century, some infant schools, following the Frobel’s method, offered a table to the children. With this in mind, the goal of this paper is to examine the contradictions that emerged when the gallery was replaced by chairs and tables in those decades. The contradictions and inconsistencies in the use of learning environments will be shown by using the last pieces of research and new archive pictures.
Presentación
Keywords: Educación - Historia; Educación infantil - Historia; History of Education; Educational Technologies; Early Childhood Education; Material culture